2013
DOI: 10.1002/macp.201300579
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Assembly of Oxidation‐Responsive Amphiphilic Triblock Polymer Containing a Single Diselenide

Abstract: Linear amphiphilic triblock polymers containing a single diselenide (SeSe‐tri‐ABP) are synthesized by coupling reactions. They self‐assemble into spherical micelles 1 in aqueous solution. A remarkable morphology transformation of the micelles is confirmed through dynamic light scattering (DLS) and transmission electron microscopy (TEM). The release behavior of a model molecule, Rhodamine B (RB), is studied by UV–vis spectrophotometry. It is found that post‐assembly from micelles 1 to micelles 2 is induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It was found that M-P-Se/DTX displayed a slow-level release rate and exhibited a lower cumulative release ratio of DTX (less than 40 % over 24 h) in the absence of GSH, and DTX was released due to the diffusion mechanism [27]. On the contrary, DTX release rate increased obviously at the presence of GSH, and higher GSH concentration induced the faster DTX release.…”
Section: In Vitro Dtx Release From M-p-se Micellesmentioning
confidence: 76%
“…It was found that M-P-Se/DTX displayed a slow-level release rate and exhibited a lower cumulative release ratio of DTX (less than 40 % over 24 h) in the absence of GSH, and DTX was released due to the diffusion mechanism [27]. On the contrary, DTX release rate increased obviously at the presence of GSH, and higher GSH concentration induced the faster DTX release.…”
Section: In Vitro Dtx Release From M-p-se Micellesmentioning
confidence: 76%
“…PySeSePy is not commercially available. Thus, we began with the synthesis of PySeSePy by first reducing elemental selenium with sodium borohydride and then introducing 2‐bromopyridine for a nucleophilic displacement reaction, using reported methodologies . The synthesis was completed giving 49% yield.…”
Section: Resultsmentioning
confidence: 99%
“…PySeSePy was synthesized following previously reported methods . Water (20 mL), in a round‐bottom flask containing 0.596 g (15.75 mmol) of sodium borohydride, was cooled on ice to 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The dialkylsulfide-based systems are mostly composed of poly(propylene sulfide) [172]. An interesting case is polymers containing diselenide bonds that are responsive to both oxidative and reductive environments [173][174][175][176] and also to gamma radiation [177].…”
Section: Redox Responsivitymentioning
confidence: 99%